2021
DOI: 10.1001/jamahealthforum.2021.2333
|View full text |Cite
|
Sign up to set email alerts
|

Association of Patient Race and Ethnicity With Differences in Opioid Prescribing by Primary Care Physicians for Older Adults With New Low Back Pain

Abstract: IMPORTANCE Substantial patient racial and ethnic differences in opioid prescribing have been documented, but how much of these differences were attributable to physicians prescribing opioids differently to patients of racial and ethnic minority groups is unknown, particularly during the first wave of the opioid epidemic when the dangers of opioid prescribing and use were not as well known. OBJECTIVETo examine associations of patient race and ethnicity with differences in opioid prescribing by the same primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…24,[29][30][31] Given that these patients did not report significantly different amounts of pain by race, it is important to investigate whether the factors driving this variation are patient versus physician-driven or whether they are mostly system-level factors. 29,32,33 Since pain management is a complex subject especially among patients with cancer, the drivers of the racial disparities in pain prescriptions seen in the current study could be similarly convoluted. 34,35 Previous studies have suggested that patients' pain perception might differ on the basis of sociodemographic characteristics, as well as differences in patient-physician communication, decision making, health literacy, and other social determinants of health.…”
Section: Discussionmentioning
confidence: 85%
“…24,[29][30][31] Given that these patients did not report significantly different amounts of pain by race, it is important to investigate whether the factors driving this variation are patient versus physician-driven or whether they are mostly system-level factors. 29,32,33 Since pain management is a complex subject especially among patients with cancer, the drivers of the racial disparities in pain prescriptions seen in the current study could be similarly convoluted. 34,35 Previous studies have suggested that patients' pain perception might differ on the basis of sociodemographic characteristics, as well as differences in patient-physician communication, decision making, health literacy, and other social determinants of health.…”
Section: Discussionmentioning
confidence: 85%
“…This may indicate that the OUD consult service can provide further benefit to trauma teams via input on managing co-occurring pain and OUD while patients are hospitalized, although further research controlling for variables such as injury severity and race/ethnicity (because of the potential for provider bias) is needed. 23,24 Patients with OUD may experience withdrawal symptoms in addition to pain from injuries, and so the use and titration of methadone and buprenorphine (both for pain and withdrawal management), as well as guiding use of full-agonist opioids, may help to achieve better pain control and lessen patient withdrawal-related discomfort. 25,26 Provision of opioids for acute pain management in patients with OUD can be challenging, as these patients will likely require higher doses of opioids to maintain adequate pain control than those who are opioid naive.…”
Section: Discussionmentioning
confidence: 99%
“…While not statistically significant, a greater proportion of individuals in the consult group (59.3%) were discharged with non-MOUD full-agonist opioids than those in the nonconsult group (43.8%), even though similar proportions received opioids during hospitalization (92.6% and 90.6%, respectively). This may indicate that the OUD consult service can provide further benefit to trauma teams via input on managing co-occurring pain and OUD while patients are hospitalized, although further research controlling for variables such as injury severity and race/ethnicity (because of the potential for provider bias) is needed 23,24 . Patients with OUD may experience withdrawal symptoms in addition to pain from injuries, and so the use and titration of methadone and buprenorphine (both for pain and withdrawal management), as well as guiding use of full-agonist opioids, may help to achieve better pain control and lessen patient withdrawal-related discomfort 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…17,21,22,39 Furthermore, studies on disparities in the provision of treatment have found that Asians experience disadvantages in certain realms of care, especially those involving subjective or affective input. For example, research finds Asian individuals to be least likely to receive prescription analgesics for pain, 40 be hospitalized for cardiovascular illnesses, 41 or receive diagnostic testing for the comorbidities of diabetes, after adjusting for need. 42 Hence, although Asians are regarded as "model minorities" and shown to be as healthy as their White counterparts on various health outcomes, 43,44 our findings, together with prior research, lend further support for the need to closely examine race-based disadvantages experienced by Asian individuals, the fastest growing population subgroup in the United States.…”
Section: Discussionmentioning
confidence: 99%